Spatial and temporal variability of CO2 emisions in soils under conventional tillage and no-till farming - Carbonell-Bojollo, R. (2013)
Agricultural soils can act as a carbon sink depending on the soil management practices employed. As a result of this functional duality, soil management systems are present in international documents relating to climate change mitigation. Agricultural practices are responsible for 14% of total greenhouse gas emissions (GHG’s) (MMA, 2009)(1). Conservation agriculture (CA) is one of the most effective agricultural systems for reducing CO2 emissions, as it increases the sequestration of atmospheric carbon in the soil. In order to assess the performance of CA in terms of CO2 emissions, a field trial was conducted comparing soil derived CO2 fluxes under No-till (NT) farming and under conventional tillage. Three pilot farms were selected in the cereal-growing area of southern Spain, located in Las Cabezas de San Juan (Seville), Carmona (Seville) and Cordoba. Each pilot farm comprises six experimental plots with an approximate area of five hectares; three of the six plots implement CA practices, while the other three use conventional tillage techniques. The subdivision of each tillage system into 3 plots allowed the simultaneous cropping of the three crops of the wheat-sunflower-legume rotation each year. Results showed that carbon dioxide emissions were 31 to 91% higher in tilled soils than in untilled soils, and that there was a great seasonal variability of CO2 emissions, as weather conditions also differed considerably for the different sampling periods. In all cases, the CO2 fluxes emitted into the atmosphere were always higher when soil was subject to conventional tillage.